Hamka’s Interpretation of Qur’anic Rebuke (‘Itāb) Verses: Cultural Reflections on Islam in West Sumatra - Ahmad Bahrul Hikam; Mohamad Zaenal Arifin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
The interpretation of the verses of ‘itāb (divine rebuke) in the Qur’an is not only normative-theological, but also has a cultural content that can reflect local values. This article aims to analyze Hamka’s interpretation of ‘itāb verses (such as QS. Abbas/80: 1-4, QS. at-Tahrīm/66: 1-5, QS. al-Anfāl/8: 67–68, and QS. al-Ahzāb/33: 37) in Tafsir Al-Azhar, as well as how the interpretation reflects the Islamic philosophy and identity of the Minangkabau people. Using the literature study method and content analysis approach, this study explores how the verses of ‘itab are interpreted by Hamka in the context of local culture based on the philosophy of Basandi Syarak Syarak Basandi Kitabullah Customs. The results of the study show that Hamka not only interprets Allah’s rebuke as a theological correction, but also as a social ethics in accordance with Minangkabau philosophy, such as duduak samo randah-tagak samo tinggi, raso jo pareso, abstinence from the property of the position, bundo kanduang, and kato nan ampek. The local philosophy emphasizes social equality, sensitivity and scrutiny, integrity and social responsibility, the important role of women, and language ethics. These findings show that culturally responsive local interpretations can extend the normative meaning of the Qur’an into society’s moral praxis. This study recommends strengthening culturally based contextual interpretations in Islamic education and Qur’an studies.